2020
DOI: 10.1016/j.drugpo.2020.102854
|View full text |Cite
|
Sign up to set email alerts
|

Association of alcohol control policies with adolescent alcohol consumption and with social inequality in adolescent alcohol consumption: A multilevel study in 33 countries and regions

Abstract: Highlights A combined alcohol control policy showed to be effective in reducing teen drinking. The combination can also tackle socioeconomic inequalities present in teen drinking. Single measures were in general not associated with decreases in teen drinking. Alcohol pricing policy showed to be the most successful single measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“…Our results showed a positive and significant trend to decrease the consumption (any use, independently of frequency, or quantity), among boys and girls, across time. Our results corroborate a sex difference (boys consume more than girls) and an increase with age also observed in other studies ( 31 , 32 ). Among adolescents, the social environment influences health behaviors mainly related to alcohol and smoking.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed a positive and significant trend to decrease the consumption (any use, independently of frequency, or quantity), among boys and girls, across time. Our results corroborate a sex difference (boys consume more than girls) and an increase with age also observed in other studies ( 31 , 32 ). Among adolescents, the social environment influences health behaviors mainly related to alcohol and smoking.…”
Section: Discussionsupporting
confidence: 93%
“…However, the investigation by Leal-López et al [63] in 33 countries with adolescents between 11 and 15 years old concluded that living with families of high material affluence represents a risk factor for increased alcohol consumption. In fact, among adolescents of 18 with high wealth levels, factors such as excessive pressure for goal achievement and their parents' emotional and physical distance make them vulnerable to substance abuse, depression, and anxiety than those of medium or low-income levels [64].…”
Section: Family Context Factors Of External Regulation: the Socio-educational Level Of Parentsmentioning
confidence: 99%
“…In this sense, some studies have detected inequalities in trends in alcohol consumption regarding sex, socioeconomic status or native/immigrant. 35–38 A recent study conducted with HBSC data showed that, despite the confirmed overall downward trend in adolescent alcohol use between 2002 and 2014, socioeconomic inequalities related to family material affluence (higher lifetime use, weekly drinking and drunkenness among adolescents from a higher position) and perceived family wealth (higher drunkenness among adolescents who perceived their families to be poor) persisted in lifetime and weekly use and even increased in drunkenness. 35 At regional- and country-level, future studies should analyze the reasons why specific countries have not decreased over time, or even while decreasing in some behaviours, have remained among the most prevalent in others.…”
Section: Discussionmentioning
confidence: 98%
“…taxation and price regulation) have stood out as one of the most effective measures. 29 , 34 , 35 Efforts should be focused not just on what may be related to the decrease, but also on exploring why the decline is present only (or to a larger extent) in some groups of adolescents and not others. In this sense, some studies have detected inequalities in trends in alcohol consumption regarding sex, socioeconomic status or native/immigrant.…”
Section: Discussionmentioning
confidence: 99%